Corrigendum to: The Daugavet property for spaces of Lipschitz functions - Ivakhno, Yevgen; Kadets, Vladimir; Werner, Dirk (MATHEMATICA SCANDINAVICA, 2009)
Corrigendum to our paper The Daugavet property for spaces of Lipschitz functions, Math. Scand. 101 (2007), 261-279.